Factors influencing the purchasing of affordable housings: Housing purchasers’ perspective - Eng, Zheng Feng (2021)
The housing affordability crisis has been a severe issue in Hong Kong, London, Sydney, and including Malaysia. The purchase of unaffordable houses causes household stresses, strain to physical and mental health, and impeding the growth of the economy. On the other hand, the provision of affordable housings by the government was unattractive in terms of its attributes. Numerous studies were conducted on the preferences of housing in Malaysia. However, there are limited studies dedicated to the preferences of affordable housings from B40 and M40 house purchasers’ perspectives. Therefore, this study aims to investigate the factors influencing the purchasing of affordable housings by house purchasers which sets out the purchasing requirements of housing purchasers in selecting and purchasing affordable housings. There are four main attributes identified in this study that influencing the purchasing of affordable housings, which are financial, general, accessibility, and neighbourhood. Questionnaires were distributed to B40 and M40 house purchasers and 119 responses were collected. Data obtained were analysed by Cronbach Alpha Reliability Test, Arithmetic Mean, Mann-Whitney U Test, and Kruskal-Wallis. This study discovered that house purchasers would prioritise financial attribute more than other attributes when purchasing affordable housings. This study also revealed that different social demographics house purchasers have different prioritisation in purchasing affordable housings. The findings of the research are useful to policymakers, local and housing authority, and property developers in the provision of affordable housing with attributes that are aligned with the preferences to house purchasers.